НЕКИ АСПЕКТИ НАСТОЈАЊА ПОЛИТИЧКОГ ЗАПАДА: ИЗАЗОВИ МОЋИ И СУПРЕМАТИЈЕ - Ivanov, Ivan (Srpska politička misao, 2025)
This paper explores the transformation of global power structures in the context of the perceived decline of American hegemony and the liberal international order. It critically assesses the internal and external pressures reshaping the U.S.-led global framework, including ideological fragmentation within liberal democracies, the strategic rise of non-Western actors such as China and Russia, and the growing challenges to the legitimacy of multilateral institutions. The concept of the “Political West” is used to describe the alliance of liberal democracies committed to open markets, democratic governance, and rule-based international norms. By analyzing key theoretical perspectives and geopolitical developments, the study aims to evaluate whether the current world order is undergoing a temporary adjustment or a more enduring systemic transition toward multipolarity.